Insights into the textural properties and starch digestibility on rice noodles as affected by the addition of maize starch and rice starch. (1st January 2023) - Geng, Dong-Hui; Tang, Ning; Zhang, Xiaojun; Zhao, Minhao; Jia, Xin; Cheng, Yongqiang
Abstract: The effects of maize starch (MS) and rice starch (RS) addition on rice noodle quality were investigated, aiming to develop high-quality noodles with both desirable textural properties and low starch digestibility. The results showed that the MS had more short branch chains and higher branch density when compared to RS, and the final viscosity and gel strength of rice paste decreased with its addition. The textural properties between rice noodles with less than 20% MS and without MS did not differ significantly, while the network structure of rice noodles with more MS was significantly weakened due to the steric hindrance of short branch chains. The addition of RS increased the texture quality of rice noodles. Moreover, their addition reduced the estimated glycemic index of rice noodles, because more starch promoted the arrangement of starch chains and formed ordered double helix. The MS with more short chains was conducive to the formation of double helix to reduce digestion rate, and the RS with more long chains formed stabler gel and crystal structures to reduce digestible starch content. Therefore, MS and RS addition had potential to produce rice noodles with high comprehensive quality, and MS content should be controlled below 20%. Highlights: Compared with rice starch (RS), maize starch (MS) had more short branch chains. Adding 20% MS hardly changed the texture quality of rice noodles. MS and RS addition increased ordered molecular structure and reduced eGI value. MS addition formed more double helix structure and reduced starch digestion rate. RS addition increased texture quality and reduced digestible starch content.